Exposing Pharmacy Students to Public Health Concepts through Volunteering in the Medical Reserve Corps - Hunter O. Rondeau; Robert L. Emerson; Natalie R. Gadbois (University of Minnesota Libraries Publishing, 2022)
Pharmacy students at the University of Kansas School of Pharmacy's regional campus were exposed to the Medical Reserve Corps (MRC), a volunteer-based network that organizes locally to improve the health and safety of their communities. The school partnered with the local Medical Reserve Corps to provide students' opportunities to fulfill co-curricular requirements and facilitate an application-based learning environment for public health concepts. The objective of the study was to explore the relationship between volunteering in the MRC and pharmacy students' ability to meet educational outcomes and reinforce beliefs about their profession's role in public health. Twenty-one students completed a survey addressing their ability to meet educational outcomes and identify the role of pharmacists in public health. Pharmacy students strongly agreed their past participation (mean 4.57) and future volunteering (mean 4.48) within the MRC would continue to help them better understand their role in public health. Pharmacy students strongly agreed (means ranging from 4.43 to 4.71) that they were able to fulfill educational outcomes related to knowledge, skills, and attitudes pharmacy graduates should possess. The positive responses gathered warrants expanding the partnership to include more student healthcare disciplines as well as looking for further opportunities to engage students in public health initiatives. Pharmacy schools should look to adopt similar partnerships with MRC units.